2014
DOI: 10.1093/icb/icu001
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Regulation of Bone and Energy Metabolism in Hibernating Mammals

Abstract: Precise coordination among organs is required to maintain homeostasis throughout hibernation. This is particularly true in balancing bone remodeling processes (bone formation and resorption) in hibernators experiencing nutritional deprivation and extreme physical inactivity, two factors normally leading to pronounced bone loss in non-hibernating mammals. In recent years, important relationships between bone, fat, reproductive, and brain tissues have come to light. These systems share interconnected regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 209 publications
(269 reference statements)
0
16
0
Order By: Relevance
“…In grizzly bears, this maintenance is achieved despite a decrease in bone turnover (191), presumably by balanced reductions in the activities of both osteoblasts and osteoclasts. From a recent review (80), however, it is evident that the regulation of this balance in hibernation is complex and not yet fully understood.…”
Section: Do Hibernators Resist Atrophy?mentioning
confidence: 99%
“…In grizzly bears, this maintenance is achieved despite a decrease in bone turnover (191), presumably by balanced reductions in the activities of both osteoblasts and osteoclasts. From a recent review (80), however, it is evident that the regulation of this balance in hibernation is complex and not yet fully understood.…”
Section: Do Hibernators Resist Atrophy?mentioning
confidence: 99%
“…Thus, leptin could contribute to the control of balanced bone remodelling during hibernation and aestivation. In hibernators, serum leptin usually peaks during the autumn as a result of increased food intake in preparation for dormancy (Doherty et al, 2014). Elevated concentrations of leptin during pre-hibernation and early hibernation have been documented in species such as bears, woodchucks, marmots and ground squirrels (see Doherty et al, 2014, and references therein), before the level of leptin gradually drops well into the hibernation season.…”
Section: Mechanisms Underpinning the Inhibition Of Osteoporosismentioning
confidence: 99%
“…In hibernators, serum leptin usually peaks during the autumn as a result of increased food intake in preparation for dormancy (Doherty et al, 2014). Elevated concentrations of leptin during pre-hibernation and early hibernation have been documented in species such as bears, woodchucks, marmots and ground squirrels (see Doherty et al, 2014, and references therein), before the level of leptin gradually drops well into the hibernation season. It has been suggested that suppressed bone resorption in hibernating black bears may be due to leptin-mediated stimulation of hypothalamic CART (Seger et al, 2011).…”
Section: Mechanisms Underpinning the Inhibition Of Osteoporosismentioning
confidence: 99%
“…The marmots were synchronized in January so they would all be on the same torpor bout schedule, and necropsy could be scheduled for midtorpor as opposed to during interbout arousal, when metabolism increases for short durations. The stage of hibernation may contribute to variations in the physiology of bone remodeling processes (Doherty et al 2014). It is possible that one or more of the marmots were out of sync and were entering or exiting a torpor bout (i.e., at a higher metabolic state) at the time of sample collection, and this may explain some of the outlying values we found.…”
Section: Discussionmentioning
confidence: 92%